PKM BAHAYA PAPARAN EDUKASI LOGAM BERAT PADA KRIM PEMUTIH WAJAH - Diana Apriani (Pusat Riset dan Inovasi Nasional, 2021)
Many choices of cosmetic products to make women look more beautiful. One of them is a facial whitening cream (Whitening Cream). However, it turns out that there are still many face creams that contain heavy metal compositions, one of which is hydroquinone. This community service activity aims to provide education to the community in an effort to minimize the use of whitening creams that are dangerous to contain heavy metals. The activity was carried out in RT.02/RW.01 Rawabuaya Village. Through this activity, the identification of heavy metal content in facial creams is carried out by detecting hydroquinone using nonikit. The identification stage is by dripping a little cream and then adding 2 drops of nonikit, then seeing the color change. The results of testing on several cosmetic brands used by the public, there are 5 positive trademarks containing hydroquinone from the facial cream used. Brands indicated to contain hydroquinone are Fair & lovely (30%), Kinclong (50%), BioAqua (30%) and RK Glow (50%), SP Strong (50%). Face creams that have been identified as positive for heavy metals should be discontinued because they will cause serious health effects. This activity has a positive impact on the community to be more careful in choosing the use of facial creams.